A futuristic view of using XBRL technology in non-financial sustainability reporting: The case of the FDIC - Rania Mousa; Peterson K. Ozili (Journal of Risk and Financial Management, 2023)
The rapid use and development of information and communication technology capabilities in the public sector has revolutionized the mechanism that government agencies use to collect, process, and disseminate data. Electronic government is one of the strategic initiatives that many government agencies have considered adopting to offer efficient web-based services and operations. Although there have been efforts to examine the implementation process of technological innovations in financial and business reporting, many government agencies are about to face a bigger challenge in developing or adopting current technologies to assess their usefulness for non-financial sustainability reporting. The Extensible Business Reporting Language, XBRL, has been adopted by the U.S. Federal Deposit Insurance Corporation (FDIC) to process financial data in the quarterly call reports filed by banks. Using Rogers' well-established theory of innovation adoption process, this paper discusses the FDIC's XBRL implementation process and investigates the roles and experiences of the agency's stakeholders. A case study research methodology, supported by semi-structured interviews, is used to explore each phase of the implementation process. The findings reveal that the process was facilitated by stakeholder engagement, technical support, and the agency's strategic decision-making process. This paper contributes to the literature by examining the applications, benefits, and challenges of using XBRL technology to process non-financial sustainability data, which is still an under-researched area. Therefore, the implications for using the technology in non-financial reporting will be insightful for future regulatory adopters and their stakeholders including filer banks, software vendors, and various users of financial and non-financial information.
Keywords: 650; Federal Deposit Insurance Corporation (FDIC); United States; Extensible Business Reporting Language (XBRL); e-government; sustainability; non-financial reporting